Discrete element modelling of one-dimensional compression of cemented sand - de Bono, John P.; McDowell, Glenn R. (Springer Verlag, 2014)
It has recently been shown that the one-dimensional normal compression of sand can be modelled effectively in three-dimensions using the discrete element method, and that the slope of the compression curve (in log voids ratio–log stress space) is controlled by the size effect on average particle strength. This paper incorporates soil structure by simulating cemented sand, and the effects of inter-particle bonding (including bond strength and strength distributions) on the one-dimensional compression behaviour and evolving particle size distributions are investigated. The results show that bonding reduces particle crushing, and it is both the magnitude and distribution of bond strengths that influence the compression curve of the structured material.